Prehospital management of aortic dissection - Preveden, Andrej; Majdevac, Slavica; Detki, Mihaela; Mladenović, Nikola; Okiljević, Bogdan; Šušak, Stamenko (Scripta Medica, 2019)
Medical staff that makes the initial contact with patient with aortic dissection has a goal to rise a suspicion and recognize aortic dissection, as well as to safely transport the patient to a health center capable of providing the definite treatment. First step in the prehospital management is providing oxygen support via breathing mask to prevent organ damage. It is important to monitor all vital functions during transport, including heart rhythm and diuresis, in order to have a continuous insight into the patient’s current state and in case of a deterioration react appropriately. Blood pressure control is the main goal of the medical treatment in aortic dissection. Systolic blood pressure should be kept between 100-120 mmHg, whereas the target heart rate is 60 beats per minute. Therapy should be started with intravenous administration of beta-blocker or non-dihydropyridine calcium channel blocker, followed by a vasodilator infusion. For pain management intravenous administration of opiates is recommended. In case of shock, intravenous fluid replacement with crystalloids should be initiated immediately, along with vasopressor therapy with noradrenalin or phenylephrine. In case of shock, the patient should be intubated and mechanically ventilated with the appropriate sedation.